Real exchange rates and real wages in Peru: 1971-1987 - Oliva Neyra, Carlos Augusto (1989)
​The relation between the exchange and labour market, through the real exchange rates and real wages, in the case of Peru 1971-1987, is intended to be defined and quantified in this article. We will discuss the inverse relationship between both variables, as well as the effects of different economic policies which support this relation, trying to demonstrate that the indexation of the exchange rate for Peru, is a maningless cost alternative for the worker.